Juventude, formação e trabalho: um estudo com jovens das camadas populares - Meneses, Branca Maria de (2007)
The apprehension of values concerned to the relation between formation and work, under the point of view of workers and students of the popular layers, is the research subject of this thesis. The interest in understanding the meaning attributed to this relation aimed at verifying the possible ways of autonomy expression of those youngsters or how they are adapted to the rules established by the society. The universe of this research, are youngsters aged between 15 and 17 years old that in 2006 participated in the Program of Professional Formation at Instituto Mirim de Campo Grande/MS, from which was extracted a sample of two hundred youngsters, based on the Formation and Work Scale, prepared according to the Likert method, and validated by the author. The subjects that comprise this instrument are subdivided in four sub-scales: work conception; attitudes valued at work; value given to the school education and work; adaptation to the ideology of the managed world. The contents that guide the questions of sub-scales proposed were established based on studies of authors of the critical theory of the society, as well as on researches that approached the concept of youth, work and formation. The results obtained confirmed the assumption that the individuals of the research, while answering the items about the relation between formation and work, they expressed in their choices the prevalence of values that appoint agreement to the logics managed by the capital. However, it was no possible to prove the assumption that those youngsters value more the formation resulting from experiences lived at work, instead of that one obtained in the school formation. In general, it is possible to state that, despite there is unequivocally the weight of the contradiction in the thoughts of those youngster, there are indicative attitudes of reserved resistances, in the sense of having contrapositions and, at the same time, harmony with the values of the social dominating system